PENERAPAN METODE EJA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 MI PADA MATA PELAJARAN BAHASA INDONESIA DI MI MIFTAHUL HUDA KOTA TASIKMALAYA - Nur Islamy, Astri (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
It is a fact that humans use language as a tool to communicate with other people orally and in writing, so that language plays an important role in the learning process. Therefore, teachers try to use good and correct language so that students can emulate it. This study aims to find out how the spelling method is applied to improve the beginning reading skills of grade 1 students at MI Miftahul Huda, Tasikmalaya City. This study used a qualitative approach using interview, observation, and documentation methods to evaluate the application of the spelling method in improving the beginning reading skills of grade 1 MI students in the Indonesian subject at MI Miftahul Huda, Tasikmalaya city. The research was conducted by involving 25 grade 1 MI students as research subjects. Data was collected through interviews with Indonesian teachers, direct observation of the learning process, and documentation of student learning outcomes. Data analysis was carried out by identifying themes that emerged from the results of interviews and observations. The results showed that the application of the spelling method had a positive impact on improving students' beginning reading skills. Through this method, students become more skilled at recognizing letters, reading syllables, and reading simple words. In addition, the spelling method also increases students' motivation and interest in learning Indonesian. This study concludes that the application of the spelling method through a qualitative approach can be effective in improving the beginning reading skills of grade 1 MI students in the Indonesian language subject at MI Miftahul Huda, Tasikmalaya city. This method provides in-depth insight into the learning process and students' experiences in learning to read.